«El beso de Evans»: The influence of dandyism in a story by Abraham Valdelomar - Palacios Valverde, Tadeo (2022)
This article is based on the study of the story «El beso de Evans: un cuento cinematográfico», written and published by Abraham Valdelomar in 1911 and included in the famous story El caballero Carmelo, of 1918. The objective of the text is to reflect on the figure -to a certain extent relegated or anecdotalof the author as a dandy; and, likewise, to verify and to evidence the determinant influence that dandyism had in the creation of this particular literary piece of the author from Iquique. For this purpose, we first focus on the critical notion of the split and the dichotomy that tries to isolate the canonical Valdelomar, of traditional Creole work, from his dandy performative facet; and then we will proceed to check if this is univocally valid (or desirable) for the study of his literary work.